REVITALISASI PENDIDIKAN BAHASA MELALUI SYLLABIC METHOD DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS 1 B SD IT SALSABILA - Aisya Rahma Fadhilla (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
Reading and writing are important basic academic skills. Even so, it turns out that quite a lot of elementary school students in Indonesia have not mastered it. The child's ability to recognize words when reading is influenced by the teaching method or teaching method used by the teacher. This research is based on the opinion that when students are taught using techniques or methods that suit their learning style, they will find it easier, faster, and can retain and apply concepts more easily for further learning. The subjects in this study were nine students of grade 1 B at SD IT Salsabila 3 Banguntapan who showed less achievement in reading than their peers. In this regard, to train and improve beginning reading skills in grade 1 students. The method used is the Syllabic Method (Syllabic Method). The syllable method is a method that starts teaching reading beginning by presenting words that have been assembled into syllables, then the syllables are arranged into words. The results of this study indicate that in carrying out initial reading through the Syllabic Method with the help of the AHE (Great Boy) book, students are expected to be able and easily recognize letters, syllables, and sentences in order to improve their reading skills.